KAJIAN MAKNA, NILAI DAN BENTUK LAGU TAWAR SEDENGE SEBAGAI LAGU SELINGAN DALAM UPACARA NASIONAL DI SMP NEGERI 1 TAKENGON KABUPATEN ACEH TENGAH - Jayanti, Amalia Putri (Universitas Negeri Medan, 2017)
Assessment Form, Meaning, Value song TawarSedenge As song interlude in National Ceremony in junior high school 1 CentralAceh district. Essay. Sendratasik majors. Music Education Program. Faculty ofLanguage and Art. Medan State University in 2015. This study discusses themeaning, value and form Tawar Sedenge song as the song interlude at a nationalceremony. The research was conducted in order Gayo society, especially theyounger generation can understand the meaning, value (meaning is the intentionof the song lyric bargaining sedenge, while the value is to assess the meaning of ameaning) and the form of songs bargaining sedenge as anthem Gayo people whoalways sung on the great days, especially at the national ceremony in SMP Negeri1 Takengon, Central Aceh district. The theory used in this research is the theoryof meaning that examines denotative and connotative meaning, value theory,which examines the theory of form sentences, phrases and motifs, which are veryuseful in the study. The method used in this research is descriptive qualitativemethod. Research location in SMP Negeri 1 Takengon, Central Aceh district. Thesample was a song that is sung sedenge bargaining as the song interlude in anational ceremony. The technique of collecting data through observation,interviews, documentation, and laboratory work. The data analysis techniqueused is descriptive qualitative analysis method that is accompanied by thepresentation of data and drawing conclusions. According to the research done, itcan be in the know that the meaning of the song bargaining sedenge based on themeaning of denotation and connotation contains a message to the communityGayo so grateful, and welfare of the land so that people Gayo Gayo rise andvictorious from the downturn. The value contained in the song bargainingsedenge adalan value can increase the sense of nationalism is love of thehomeland, which are vital values (education) and the spiritual (religious, beauty,culture) that have been arranged in a hierarchy. Tawar Sedenge song form thatAABBAABB, consisting of 2 forms or themes that form a sentence and thesentence B.